Retinitis Pigmentosa: A Case Report - Delfi Delfi; Vanda Virgayanti; Rika Ramadhani Sinambela (Jurnal sosial dan sains, 2022)
Background : Retinitis pigmentosa is an inherited heterogeneous group of retinal disorders represented by rod photoreceptors progressive dysfunction with subsequent cone photoreceptors degeneration and the retinal pigment epithelium. The typical manifestations are progressive loss of visual field and night blindness. Purpose : The purpose of this study was to examine with the Amsler Grid on the right and left eyes, no scotomas and metamorphopsia were found. Method : The type of research is quantitative with an explanatory research approach, the sampling technique is saturated sampling with the number of subjects 76 employees and the data analysis technique uses PLS. Results : Best corrected visual acuity was 6/9 in the right eye and 6/18 in the left eye. There was arteriolar attenuation, waxy disc pallor, bone-spicule pigmentation and pigment deposits on both eyes in funduscopy exaination. The patient was diagnosed with retinitis pigmentosa. The management given was vitamin A 15.000 IU/day, DHA 1.200mg/day, and counselling about retinitis pigmentosa, progressivity, and prognosis. Conclusion : Retinitis pigmentosa caused irrreversible visual and visual field impairment. Low vision management for retinitis pigmentosa was to optimize the visual function and optimized quality of life. Genetic counselling might provide the patient and her family information of the inheritance and genetic disorders implications that could help the patient to obtain medical information regarding the disease.